Case report: Gross total resection of a primary fourth ventricular meningioma using the telovelar approach in a dog - Jeong, Jaemin; Lee, Haebeom; Rho, Yoonho; Jeon, YoungJin (Frontiers in Veterinary Science, 2024)
An 11-year-old spayed female Maltese dog presented with a 2-month history of gait alterations, wide-based stance, and chronic vomiting. Neurological examination revealed cerebellovestibular signs, including head tilt, nystagmus, strabismus, intentional tremor, and hypermetric gait. MRI showed a mass with iso- to hypointensity on T1-weighted (T1W) images and heterogeneous hyperintensity on T2-weighted (T2W) images, with marked non-uniform contrast enhancement. The tumor was removed via a telovelar approach without intraoperative complications. Postoperatively, the dog developed non-ambulatory paraparesis with the rigidity of the pelvic limbs but recovered ambulation within 6 days. Preoperative neurological signs progressively improved, and the patient was discharged without complications 10 days after surgery. Histological examination revealed dense spindle cells with an abundant collagen matrix and oval-shaped nucleated cells with small whorls, leading to a diagnosis of transitional meningioma of the fourth ventricle. MRI follow-up at 8 months postoperatively showed no definitive evidence of recurrence. At the final follow-up, 15.4 months postoperatively, mild neurological signs, including a slight head tilt and subtle strabismus, remained, but the rest of the neurological examination was normal. This is the first reported case of a meningioma in the fourth ventricle of a dog successfully removed using the telovelar approach.